455Association of interpregnancy interval and preterm births: what does a sibling-matched study indicate?. (2nd September 2021) - Tessema, Gizachew; Marinovich, M Luke; Håberg, Siri E; Gissler, Mika; Mayo, Jonathan A; Nassar, Natasha; Ball, Stephen; Betrán, Ana Pilar; Gebremedhin, Amanuel T; de Klark, Nick; Magnus, Maria C; Marston, Cicely; et al.
Abstract: Background: Most evidence for interpregnancy interval (IPI) and adverse birth outcomes come from between-women (unmatched) studies that are prone to incomplete control for confounders that vary between women. Comparing pregnancies to the same women (sibling-matched) can address this issue. Methods: We conducted an international longitudinal study of births from Australia, Finland, Norway, and United States (California) covering over three decades (1980-2017). We included 5, 523, 914 births to 3, 849, 737 women, and within each country, we first investigated the associations between IPI and preterm birth (PTB), spontaneous PTB using logistic regression (unmatched analyses). Second, we used conditional logistic regression comparing IPIs in the same women (sibling-matched analyses), with 2, 908, 907 births to 1, 234, 730 women having at least two IPIs. Random effects meta-analysis was used to calculate pooled effect estimates. Results: Compared to an IPI of 18-23 months, there was insufficient evidence of association between IPI <6 months and overall PTB (adjusted odds ratio (aOR)=1.08, 95%CI 0.99-1.18) but increased odds of spontaneous PTB (aOR=1.38, 95%CI 1.21-1.57). We observed elevated odds of both birth outcomes associated with IPI ≥60 months. In comparison, between-women analyses showed elevated odds of adverse birth outcomes for <12 month and >24 month IPIs. Conclusions: We found consistently elevated odds of PTB following long IPIs. IPI shorter than 6 months were associated with elevated risk of spontaneous PTB, but there was insufficient evidence for increased risk of overall PTB. Key message: Current recommendations of waiting at least 24 months to conceive after a previous pregnancy, may be unnecessarily long in high-income countries.